Risk Factors Associated with The Incidence of Low Birth Weight (LBW) at Haji Makassar Hospital in January-December 2018 - Sari, Indra; Asriani; Inayah Sari, Jelita (Journal of Health Sciences, 2022)
Low birth weight babies (LBW) are newborns whose body weight at birth is less than 2,500 grams regardless of gestational age. In 2015, the incidence of LBW in Makassar City was 690 cases. By knowing the risk factors for LBW, health workers and government can perform the targeted intervention in groups with a high risk to reduce the incidence of LBW. This paper analyzes the correlation between parity, maternal age, maternal occupation, maternal education, severe preeclampsia, premature rupture of membranes, and multiple pregnancies with the incidence of LBW. This study was analytical survey research with a cross-sectional approach. It was conducted at Haji Makassar Hospital for one month, using medical record data (secondary data). The population was 955 people who gave birth at the Haji Makassar Hospital in January-December 2018. Furthermore, the sample was 496 respondents with a purposive sampling technique. The bivariate analysis utilized the chi-square test. There was a significant correlation between parity (p=0.000), severe preeclampsia (p=0.000), and multiple pregnancies (p=0.000) with the incidence of LBW. Meanwhile, there was no significant association between maternal age (p=0.134), maternal occupation (p=0.398), maternal education (p=0.306), and premature rupture of membranes (p=0.956) with the incidence of LBW. In conclusion, risk factors for LBW are parity, severe preeclampsia, and multiple pregnancies. Meanwhile, unrelated factors with LBW are maternal age, maternal occupation, maternal education, and premature rupture of membranes.